(untitled) (East West Medical College Journal, 2024)
Introduction: The second leading cause of death in under-five children is diarrhea. ORS is a simple and highly effective therapy for managing diarrhea. However inappropriate knowledge of preparation and lack of use of ORS leads to health hazards including increased rate of mortality and morbidity. So aim of this study to assess the knowledge, attitude, and Practice of mothers towards the use of oral rehydration solution in the treatment of acute diarrhea in children. Methods: A cross-sectional study was carried out over eight months (1st May to 30th December 2023) among 510 mothers who had children of six months to five years and had recent episodes of diarrhea. Data were collected by using a semi-structured questionnaire in face-to-face interview. Data were analyzed by using SPSS software program.Results: Among 510 mothers, 47.05% were 20-30 years old, 29.80% were below 20 years and 23.13% were over 30 years. One fourth of them had no institutional education and 36.27% had primary, 20.78% and 18.23% had secondary and tertiary level of education respectively. 40.39% were from lower socioeconomic condition, 31.97% were from middle and 27.64% from upper socioeconomic condition. 100% of family used sanitary latrine though 73.72% use safe drinking water as a preventive part of diarrhea.89.98% of mother was aware about ORS but only 75.88% used ORS in recent episode of diarrhea, among them 63.03% prepared ORS correctly and 60.98% used adequate amount. Age of mothers was not corresponds with the correct preparation and practice of ORS but socioeconomic condition and level of education carried statistically significant value. Conclusion: Knowledge and practice of ORS preparation and used of ORS in recent episode of diarrhea among the mother was unsatisfactory. Improve the Maternal education and socioeconomic status will improve ORS correct preparation and use. Mothers should be taught the importance of optimal use and correct preparation of ORS in diarrhea. EWMCJ Vol. 12, No. 1&2, January-July 2024: 43-49